Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T12:01:31+01:00
A1+a3=5
a3-a1=3


a3+a1=5
a3-a1=3


2a3=8

a3=4
a1=1

a2/a1=a3/a2

a2^2 =a1*a3

a2^2 = 4
a2=2

a2/a1=q=2

a1=1
q=2

:)
2010-02-17T12:04:27+01:00
A2+a5-a3=10
A2+a9=17
Korzystam ze wzoru an=a1+(n-1)r, to a2=a1+2-1r=a2=a1+r, i tak a3=a1+2r, a5=a1+4r, a9=a1+8r
Podstawiamy do równania
A1+r+a1+4r-(a1+2r)=10
A1+r+a1+8r=17
A1+3r=10
2a1+9r=17
a1=10-3r
2*(10-3r)+9r=17
20-6r+9r=17
3r=17-20
3r=-3 /:3
r=-1
mamy więc a1=10-3*(-10=10-(-3)=13
a2=13-1=12
a3=12-1=11
a5=13+4*-1=13-4=9
a9=13+8*(-1)=13-8=5
Sprawdzamy
A2+a5-a3=10
A2+a9=17
12+9-11=10
12+5=17
10=10
17=17